2018
DOI: 10.1016/j.bjm.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Performance of rapid tests for carbapenemase detection among Brazilian Enterobacteriaceae isolates

Abstract: The global emergence of carbapenemases led to the need of developing new methods for their rapid detection. The aim of this study was to evaluate the performance of the rapid tests for carbapenemase-producing and non-producing Enterobacteriaceae. Carbapenem non-susceptible Enterobacteriaceae from a surveillance study submitted to a multiplex real time PCR for carbapenemase detection were included in this study. The isolates were subjected to the rapid phenotypic tests Carba NP, Blue-Carba and Carbapenem Inacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
1
6
1
Order By: Relevance
“…The present meta-analysis showed that the sensitivity and specificity of Carba NP test were 0.96 and 1.00, respectively, the AUC was 1.00, and the mean DOR was 573.46 indicating a high level of overall accuracy. We also noted that one study [9] showed low sensitivity (0.63), and one study 10 demonstrated a low specificity (0.71) when they used Carba NP test for the rapid detection of carbapenemase production.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The present meta-analysis showed that the sensitivity and specificity of Carba NP test were 0.96 and 1.00, respectively, the AUC was 1.00, and the mean DOR was 573.46 indicating a high level of overall accuracy. We also noted that one study [9] showed low sensitivity (0.63), and one study 10 demonstrated a low specificity (0.71) when they used Carba NP test for the rapid detection of carbapenemase production.…”
Section: Discussionmentioning
confidence: 80%
“…Our primary searches identified 1405 articles, and from these studies, eighteen articles [8][9][10][11][19][20][21][22][23][24][25][26][27][28][29][30][31][32] met eligibility criteria and are accepted in this study. The main reasons for exclusion are : did not include original data, a reference test other than PCR was used, and the study was not reported in English.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mCIM is a reliable and simple method and has a sensitivity of 98-100% in comparison with the modi ed Hodge test and the carbapenemase Nordmann-Poirel (carba NP) test with sensitivities of 93-98% and 73-100%, respectively. Furthermore, due to being expensive of PCR, mCIM could be a suitable alternative method for detecting of carbapenemase producers [12,[31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we identi ed the presence of class 1, 2 and 3 integrons among our isolates. Carbapenemase genes are harbored on mobile genetic elements and can be disseminated to other bacteria, therefore contributing to the origin of antimicrobial resistance among Enterobacteriaceae members [32]. It is reported that class 1 integron is found in 40-70% of Gram-negative pathogens and has had a major role in widespread of antibiotic resistance [14,15].…”
Section: Discussionmentioning
confidence: 99%